Tolerability and efficacy of two doses of aerosolized albuterol in ventilated infants with BPD: A randomized controlled crossover trial - Napolitano, Natalie; Dysart, Kevin; Soorikian, Leane; Zhang, Huayan; Panitch, Howard; Jensen, Erik (Pediatric pulmonology, 2021)
Rationale Aerosolized albuterol is widely used, but its tolerability and efficacy in infants with severe bronchopulmonary dysplasia (sBPD) is not well established. Objectives To compare the tolerability and efficacy of two dose levels of aerosolized albuterol to saline placebo in infants with sBPD. Methods Single‐center, multiple‐crossover trial in 24 ventilated very preterm infants with sBPD. Albuterol (1.25 mg, 2.5 mg) and 3 ml of normal saline were administered every 4 h during separate 24‐h treatment periods assigned in random order with a 6‐h washout phase between periods. The primary outcome was the absolute change (post and pretherapy) in expiratory flow at 75% of exhalation (EF75). Secondary endpoints were changes in ventilator parameters, vital signs, and heart arrhythmia. Results Average within subject EF75 values improved with each therapy: saline placebo ( + 0.45 L/min ± 2.5, p = .04), 1.25 mg of albuterol ( + 0.70 L/min ± 2.4, p < .001), and 2.5 mg of albuterol ( + 0.38 L/min ± 2.4, p = .06). However, 1.25 mg of albuterol (0.26 L/min; 95% CI −0.19, 0.72) and 2.5 mg (−0.10 L/min; 95% CI −0.77, 0.57) produced similar changes in EF75 when compared to saline. All secondary outcomes were similar between saline and 1.25 mg of albuterol. Peak inspiratory pressure needed to deliver goal tidal volumes (7.5% relative decrease, 95% CI 2.6, 12.3) and heart rate (6.5% increase, 95% CI 2.2, 10.8) differed significantly between albuterol 2.5 mg and saline. Conclusion Albuterol at 1.25 mg and 2.5 mg, compared to aerosolized saline, did not affect EF75 in infants with sBPD receiving invasive ventilation. Greater improvement in peak inspiratory pressures with albuterol 2.5 mg suggests benefit, but close heart monitoring may be indicated.